2013
DOI: 10.2478/s11658-013-0091-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 5′-flanking region of the mouse asparagine-linked glycosylation 12 homolog gene

Abstract: Recently, we characterized multiple roles of the endoplasmic reticulum stress responsive element (ERSE) in the promotion of a unique headto-head gene pair: mammalian asparagine-linked glycosylation 12 homolog (ALG12) and cysteine-rich with EGF-like domains 2 (CRELD2). This bidirectional promoter, which consists of fewer than 400 base pairs, separates the two genes. It has been demonstrated that the ALG12 promoter shows less transcriptional activity through ERSE, but its basic regulatory mechanism has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…pathway and considered by MUGBAS as the best candidate gene associated with the C18:1 trans-6-8 trait. A study of ALG12 expression in mouse cell lines revealed different transcriptional activities related to different promoter mutations (Oh-Hashi et al, 2013). Regarding the IH breed, PIA revealed a cluster of genes in "Purine metabolism," "Pyrimidine metabolism," and "Alanine, aspartate and glutamate metabolism: NT5C2, GPT, and COX15.…”
Section: Pathway Analysis Resultsmentioning
confidence: 99%
“…pathway and considered by MUGBAS as the best candidate gene associated with the C18:1 trans-6-8 trait. A study of ALG12 expression in mouse cell lines revealed different transcriptional activities related to different promoter mutations (Oh-Hashi et al, 2013). Regarding the IH breed, PIA revealed a cluster of genes in "Purine metabolism," "Pyrimidine metabolism," and "Alanine, aspartate and glutamate metabolism: NT5C2, GPT, and COX15.…”
Section: Pathway Analysis Resultsmentioning
confidence: 99%